2019
DOI: 10.1590/0103-6440201902164
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment of Rosemary-based Toothpaste (Rosmarinus officinalis Linn.): A Randomized Controlled Double-blind Study

Abstract: The present study was to investigate the action of a toothpaste made from the extract of Rosmarinus officinalis Linn. (rosemary) in a clinical randomized, controlled, open and double-blind trial. One hundred and ten volunteers fulfilled the inclusion criteria and were randomly separated into two groups according to the toothpastes used: Group A (experimental) and Group B (control). They were assessed at baseline and 30 days after the study using the gingival bleeding index (GBI) and the plaque index (PI). Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
6
0
2
Order By: Relevance
“…The chief constituent present in essential oil camphor has an antibiofilm property, which helps to prevent plaque formation [79]. Recently, in vivo study reported a reduction in biofilm by rosemary essential oil and recommended its use in new anti-caries treatment protocols [80].…”
Section: Rosmarinus Officinalis Lmentioning
confidence: 99%
See 2 more Smart Citations
“…The chief constituent present in essential oil camphor has an antibiofilm property, which helps to prevent plaque formation [79]. Recently, in vivo study reported a reduction in biofilm by rosemary essential oil and recommended its use in new anti-caries treatment protocols [80].…”
Section: Rosmarinus Officinalis Lmentioning
confidence: 99%
“…Plaque [79], dental caries [80] Results: reduction of 38% in the risk of gingival bleeding (relative and absolute)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nesta perspectiva, Valones et al (2019) realizaram um ensaio clínico randomizado duplo cego, onde avaliaram esse mesmo dentifrício, contendo extrato de Rosmarinus officinalis, comparando-o a um creme dental fluoretado disponível no mercado. Foram aplicadas as medidas de efeito para avaliação dos resultados, onde o dentifrício, contendo extrato de alecrim, demonstrou uma redução nos riscos de sangramento gengival e presença de placa, compatíveis com os do dentifrício do mercado; concluindo assim, que a criação de um dentifrício à base do extrato de alecrim mostrou-se eficiente, consistindo numa alternativa ao controle de placa e sangramento gengival.…”
Section: Resultados E Discussõesunclassified
“…O alecrim também foi utilizado na composição de uma pasta de dentes experimental por Valones (2019), os quais relataram que o R.officinalis foi eficaz no controle do sangramento gengival e no combate da proliferação bacteriana, em comparação com os resultados obtidos em um creme dental convencional. Em estudo similar, Gonçalves (2018), desenvolveram dentifrícios para uso adulto, cujos ativos apresentaram importante atividade antibacteriana, quando comparado com os padrões.…”
Section: Alecrim (R Officinalis)unclassified